1994
DOI: 10.2165/00003088-199426050-00003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Ticlopidine

Abstract: Platelets contribute significantly to arterial-occlusive thrombosis, one of the major causes of death and disease throughout the world. Consequently, inhibiting platelet function is a potentially important therapeutic goal. Among agents that inhibit platelet function, ticlopidine shows a wide spectrum of antiplatelet activity. There have been a limited number of studies investigating the pharmacokinetic profile of the drug. However, it has been demonstrated that absorption of ticlopidine after oral administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 28 publications
1
46
0
Order By: Relevance
“…However, this observation does not automatically mean that the thiolactone metabolite of ticlopidine rather than ticlopidine itself is the major player in the mechanism-based inhibition of CYP2B6 caused by ticlopidine in vivo. Because ticlopidine has been reported to be metabolized to many metabolites both in vitro (Dalvie and O'Connell 2004) and in vivo (Desager 1994), it is quite unlikely that the thiolactone metabolite of ticlopidine would reach levels higher than hepatic levels of the parent compound. Therefore, the data suggest that the mechanism-based inhibition of CYP2B6 by ticlopidine and clopidogrel in vivo mainly arises from the first oxidation step to their respective thiolactones shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, this observation does not automatically mean that the thiolactone metabolite of ticlopidine rather than ticlopidine itself is the major player in the mechanism-based inhibition of CYP2B6 caused by ticlopidine in vivo. Because ticlopidine has been reported to be metabolized to many metabolites both in vitro (Dalvie and O'Connell 2004) and in vivo (Desager 1994), it is quite unlikely that the thiolactone metabolite of ticlopidine would reach levels higher than hepatic levels of the parent compound. Therefore, the data suggest that the mechanism-based inhibition of CYP2B6 by ticlopidine and clopidogrel in vivo mainly arises from the first oxidation step to their respective thiolactones shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo metabolic studies with ticlopidine have indicated that the principal routes of metabolism are N-dealkylation, N-oxidation, and oxidation of the thiophene ring (Tuong et al, 1981;Fraire, 1984;Desager, 1994;Noble and Goa, 1996). In vitro metabolism of ticlopidine by recombinant human P450 2C19 and 2D6 has recently led to the identification of thiophene-S-oxide dimer TSOD (M2) and 2-oxoticlopidine (M4) (see Fig.…”
mentioning
confidence: 99%
“…After testing several absorption models, we implemented a transit‐compartmental model, which provided an adequate fit. Some reports indicate that repeated ticlopidine dosing causes an increase in its half‐life suggesting an auto‐inhibition process 12. These findings are physiologically plausible due to the marked potential of ticlopidine to inhibit CYP2B6.…”
Section: Discussionmentioning
confidence: 84%
“…Ticlopidine has a complex nonlinear pharmacokinetic profile that has been recorded previously in several reports 12. Ticlopidine is metabolized to 2‐oxo‐ticlopidine primarily in the liver by CYP2B6 and CYP2C19,13, 14 and previous studies have indicated that ticlopidine half‐life is increased after multiple dosing, suggesting an auto‐inhibition of ticlopidine metabolism 12…”
mentioning
confidence: 78%